DEVELOPMENT OF VIDEO LEARNING MATERIALS ON ANIMAL AND HUMAN MUSCULAR ORGANS - Elma, Elma; Hendra Nelva Saputra; Ilcham, Ilcham (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
Today's students grow and develop in the digital era, where access to various information via electronic media has become commonplace. Therefore, the development of learning videos is not only relevant but also an urgent need to answer the characteristics of this digital generation. This research aims to create learning videos on animal and human movement organs that are suitable for use in learning. This research is development research that uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Based on the presentation of research results, information was found that learning videos on animal and human movement organs were declared suitable for use in learning with an average percentage of 85.83% from media experts, 91.66% from material experts, and 87.5% of student responses in the category worthy. These findings highlight the importance of integrating technology in education to facilitate more effective learning. Therefore, adjusting the curriculum and developing learning materials that support using video as an educational tool is necessary. Apart from that, aspects of technology accessibility and affordability need to be paid attention to so that the benefits of video-based learning can be felt equally by all students.